O significado da distribuição para os grandes bancos verejistas: análise e consequências sob o ponto de vista de marketing - Arco e Flexa, Iberê (1997)
The business of banking, specially that of large retail banks, is undergoing a radical change within the coming ten years. Technology, globalization, partnerships and the marketspace are some of the most important drivers of that change. Probably the marketspace is itself the major force behind that deep transformation. We dare to estimate that 2/3 of ali banking businesses (involving financiai intermediation) will be done through one or other of the marketspace devices, such as ATMs, EFTPOS, smart cards, digital TVs, PCs, pagers or the Internet. Traditional bank distribution, the large branches network, will diminish, while businesses done through the marketspace will be dominant. The winners will adopt the AAA concept: anytime, anywhere, anyway banks.Customers are changing their shopping and banking habits and the banks have a great opportunity to take advantage of that change. We see large retail banks in the future acting as leaders and controUersof business crossroads in the virtual space. Large networks of partner companies, within or outside of the financiai markets, will be providers of specialized products and services, while the large retail banks will act mainly as sellers or retailers of that specialized products and services. Brand, reliability, large customer base and strong knowledge of that customer base will be major competitive advantages for large retail banks. Following that is marketing strategy. Marketing and communication will adopt new concepts, known as cybermarketing, which is the world of interactive one-to-one marketing using electronic remote devices. The banks will have to leam completely new ways of attracting and retaining customers and businesses in the coming future. This thesis discusses ali those points by extensively reviewing bibliography, a plenty of recent events, the development of bank's distribution channels in Brazil and in the world, the effect of emerging technology and the impact that it has on large retail banks, specially under the point of view of marketing. We have raised ten major assumptions in this thesis: 1. People will increasingly utilize the marketspace to do their day-to-day shopping and banking transactions in the coming years. 2. The proportion of business will be carried in a proportion of 1/3 through regular marketplace channels and 2/3 through marketspace channels.3. Banking business is, in fact, undergoing a major change that means, probably, the beginning of a new business cycle. 4. Large retail banks will be positioned in the center of major trade crossroads by being true leaders of large networks of partner companies within and outside the financiai sector. 5. Large retail banks will assume the role of leaders of distribution channels through which will flow a significant share of world trade and financiai transactions. It is from this flow that will arise the major opportunities for revenues for banks. 6. Bank marketing will increasingly be more direct and communication with customers will be increasingly interactive in arder to improve customization of products and services sold. 7. Consumers will look for multiple options of goods and services through the marketspace but, for safety, will search for the reliability provided by strong banks. 8. Consumers will utilize the marketspace for convenience, easiness and price, essentially for day-to-day shopping and financiai transactions. 9. Despite the social differences and technological underdevelopment, Brazil will closely follow first world nations in the arisal of the marketspace 10.Brazilian bankable people will have access to the marketspace in no more than ten years. Some experts of the industry were deeply interviewed as well 129 bank's customers were interviewed through a random sampling questionnaire. Both bibliography, the interviews and the answers to the questionnaires have brought strong support to ali of our assumptions.